CHANGES IN THE STOMACH AFTER GASTROINTESTINAL DISEASES (International Educators Conference, 2025)
Gastrointestinal diseases often lead to significant structural and functional changes in the stomach. These alterations may manifest as mucosal damage, gastric secretion imbalance, motility disturbances, and cellular degeneration. Understanding these changes is crucial for developing diagnostic, preventive, and therapeutic strategies. This article examines the physiological and pathological modifications in the stomach following gastrointestinal diseases, supported by literature analysis and clinical observations.